Analysis of biomechanical parameters extracted from anorectal manometry of fecally-continent and incontinent patients Análisis de parámetros biomecánicos extraídos de la manometría recto-anal de pacientes con continencia e incontinencia fecal Análise de parâmetros biomecânicos extraídos da manometria anorretal de pacientes continentes e com incontinência fecal - Bianca Espindola; Chris Mayara dos Santos Tibes; Huei Diana Lee; Renato Bobsin Machado; André Gustavo Maletzke; Wu Feng Chung (Universidade de São Paulo, 2012)
OBJECTIVE: to evaluate the average resulting area from the Pressure x Time curves resulting from the manometric anorectal exam and compare it with the support capacity of voluntary squeeze. Materials and METHODS: the data set was represented by data from 11 exams from continent patients and eight exams from patients with grade III fecal incontinence. The manometric curves were delineated, and the areas and support capacity of voluntary squeeze calculated, by means of the R computer language and the algorithm developed. RESULTS: the resulting averages for support capacity of voluntary squeeze in continent patients and patients with grade III fecal incontinence were 33.07 seconds and 30.76 seconds (p>0.05) and the averages for area were 2362.04 mmHg x second and 947.92 mmHg x second (p<0.05), respectively. CONCLUSION: the average resulting area is able to differentiate continent patients from incontinent and is shown to be a possible parameter in the analysis of biomechanical behavior related to the mechanisms of anorectal continence. OBJETIVO: evaluar el área media resultante proveniente de las curvas Presión versus Tiempo pertenecientes al examen manometría rectal y afrontarla con la capacidad de sustentación. Materiales y MÉTODOS: la casuística fue representada por datos de 11 exámenes de pacientes moderados y ocho exámenes de pacientes con incontinencia fecal grado III. Por medio del lenguaje computacional R y del algoritmo desarrollado fueron delineadas las curvas manométricas y calculadas las áreas y capacidades de sustentación. RESULTADOS: los medios resultantes de la capacidad de sustentación de pacientes moderados y con incontinencia fecal grado III fueron 33,07 segundos y 30,76 segundos (p>0,05) y las de la área, 2362,04 mmHg x según y 947,92 mmHg x según (p<0,05), respectivamente. CONCLUSIÓN: el área media resultante fue capaz de diferenciar los pacientes continentes de los incontinentes y demuestra ser un posible parámetro en el análisis del comportamiento biomecánico relacionado a los mecanismos de continencia rectal. OBJETIVO: avaliar a área média resultante, proveniente das curvas pressão versus tempo, pertencentes ao exame manometria anorretal e confrontá-la com a capacidade de sustentação. MATERIAIS E MÉTODOS: a casuística foi representada por dados de 11 exames de pacientes continentes e oito exames de pacientes com incontinência fecal grau III. Por meio da linguagem computacional R e do algoritmo desenvolvido foram delineadas as curvas manométricas e calculadas as áreas e capacidades de sustentação. RESULTADOS: as médias resultantes da capacidade de sustentação de pacientes continentes e com incontinência fecal grau III foram 33,07 segundos e 30,76 segundos (p>0,05) e as da área, 2362,04 mmHg x segundo e 947,92 mmHg x segundo (p<0,05), respectivamente. CONCLUSÃO: a área média resultante foi capaz de diferenciar os pacientes continentes dos incontinentes e demonstra ser um possível parâmetro na análise do comportamento biomecânico, relacionado aos mecanismos de continência anorretal.